Gender in African NDCs: Towards Transformation - Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Presented at the AGNES-organized event at COP26, “Aligning Long-term Low Carbon Climate-resilient Development Strategies with NDCs and NAPs in the Agriculture Sector in Africa”, November 4, 2021